2010
DOI: 10.1063/1.3437041
|View full text |Cite
|
Sign up to set email alerts
|

Size dependent dynamic analysis of nanoplates

Abstract: Articles you may be interested inSize effects on electromechanical coupling fields of a bending piezoelectric nanoplate due to surface effects and flexoelectricity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(19 citation statements)
references
References 17 publications
0
18
0
1
Order By: Relevance
“…Both residual surface stress and surface elasticity effects have been incorporated in the continuum mechanical modeling of nanostructures [18,19] by using the surface elastic model provided by Gurtin and Murdoch [20] and the generalized Young-Laplace equation. The surface elastic model and generalized Young-Laplace equation have been wieldy application in investigating the influence of surface effects on the mechanical responses of nanostructures, such as nanobeams [21][22][23][24] and nanoplates [25][26][27]. Recently, some researchers investigated the pull-in instability of nano-switches with consideration of surface effects, and found that surface effects made a major contribution to the pull-in instability of electrostatically actuated nanobeams [9,[28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Both residual surface stress and surface elasticity effects have been incorporated in the continuum mechanical modeling of nanostructures [18,19] by using the surface elastic model provided by Gurtin and Murdoch [20] and the generalized Young-Laplace equation. The surface elastic model and generalized Young-Laplace equation have been wieldy application in investigating the influence of surface effects on the mechanical responses of nanostructures, such as nanobeams [21][22][23][24] and nanoplates [25][26][27]. Recently, some researchers investigated the pull-in instability of nano-switches with consideration of surface effects, and found that surface effects made a major contribution to the pull-in instability of electrostatically actuated nanobeams [9,[28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the linear surface elasticity theory developed by Gurtin and Murdoch,11 the size-dependent properties of nanostructures originating from the surface effects have been widely investigated by the modified continuum models from both static and dynamic perspectives. [12][13][14][15][16][17][18][19][20] Recently, a more comprehensive and accurate model with the consideration of the effects of surface stress and surface elasticity was developed by Olsson and Park 21 to calculate the flexural rigidity of nanowires from three-dimensional elasticity theory. The distinguished feature of that model lies in the fact that it incorporates the heterogeneous nature of elasticity across the nanowire cross section.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al [40] followed this approach to derive the generalized differential equations of static, dynamic, and stability of ultra thin films including surface effects. Assadi et al [41] modified the laminated plate theory to include the effects of surface properties and temperature on the dynamic behavior of rectangular nanoplates. Farshi et al [37] studied the size-dependent flexural vibration of nanotubes with consideration of surface effects using a modified beam theory.…”
Section: Surface Effects On Flexural Wave Propagation In Nanobeamsmentioning
confidence: 99%